Portfolio of mining commodities and its incidence in exports. Peru: 2008-2017 - Gomero Gonzales, Nicko Alberto (2019)
Objective: the objective of the study is to determine how the prices of mining commodities exert influence on exports and determine the degree of correlation between prices and volumes exported. Method: the study is a descriptive, correlational, and non-experimental research. In order to carry out the respective contrasts, official information processed by the Ministry of Energy and Mines of Peru was collected and only secondary and historical information was used. Results:  After the information was processed and analyzed, it was determined that the prices of the product portfolio, due to the swings of the global market, move in the same direction, although not with perfect symmetry. Nevertheless, the same evidence was not found with the exportable volumes since on the one hand, they present weak and in some cases negative correlations, but when contrasting prices with the value of exports, a strong correlation was found for gold, zinc, copper, but not for silver, whose correlation with the price is quite weak. Conclusion: the price of commodities follows the same path due to changes in the market, generating dispersed effects in the exports of these products.